Urinary neonicotinoid concentrations and pubertal development in Chinese adolescents: A cross-sectional study. (May 2022) - Yue, Min; Liu, Qin; Wang, Feng; Zhou, Wenli; Liu, Liying; Wang, Lu; Zou, Yong; Zhang, Liyu; Zheng, Meilin; Zeng, Shaohua; Gao, Jieying
Graphical abstract: Highlights: High detection rates ranged from 72.0% to 100.0% for all neonicotinoids. Higher thiacloprid concentration was associated with lower stage of genitalia development in boys. The joint effect of all neonicotinoids on genitalia stage in boys was found. Higher thiacloprid concentration was associated with higher stage of axillary hair development in girls. Thiacloprid, associated with pubertal development outcomes, belonged to the first-generation neonicotinoids. Abstract: Background: Animal studies suggest that exposure to certain neonicotinoids may interfere with the normal function of endocrine system in mammals. However, evidence from human studies is limited. Objectives: This study conducted a cross-sectional analysis to examine urinary neonicotinoids concentrations in Chinese adolescents and its association with pubertal development. Methods: 774 urine samples from 439 boys (median age: 13.7 years; 25th-75th percentile: 12.7-14.5 years) and 335 girls (median age: 13.7 years; 25th-75th percentile: 12.7–14.5 years) were collected for determination of ten neonicotinoids (imidacloprid, nitenpyram, acetamiprid, thiacloprid, imidaclothiz, thiamethoxam, clothianidin, dinotefuran, flonicamid, sulfoxaflor) and one metabolite (N-desmethyl-acetamiprid). Urinary creatinine was detected for concentration adjustment. Pubertal development including pubic hair, axillary hair, genitalia (boys), testicular volume (boys) and breast (girls) assessed by Tanner stages and others (spermarche, facial hair for boys and menarche for girls) were obtained by physical examination and questionnaire. Logistic and bayesian kernel machine regression were used to investigate the association between neonicotinoids concentrations and pubertal developments. Results: High detection rates ranged from 72.0% to 100.0% for all neonicotinoids. Boys and girls with thiacloprid concentration at the >75th percentile had lower stage of genitalia development (OR: 0.83, 95% CI: 0.33–0.93) and higher stage of axillary hair development (OR: 1.46, 95% CI: 1.12–3.41), respectively, compared with those at the <25th percentile. The estimate change in genitalia stage was significantly different at or above the 75th percentile concentration of neonicotinoids mixture compared to the 50th percentile concentration. No associations were found between other urinary neonicotinoids and other indicators of puberty. Conclusions: Higher thiacloprid concentration was associated with delayed genitalia development in boys and early axillary hair development in girls. Neonicotinoids mixture was negatively associated with genitalia stage in the joint effect. Given the characteristic of the cross-sectional study, our results need further confirmation of the causal relationship.